Wong-Law Emotional Intelligence Scale (WLEIS-S): psychometric properties and normative data in the Peruvian adult population - Moreyra-Ruiz, Miluska Glamis (2023)
In this study, we aimed to analyze the psychometric properties of the WLEIS-S Scale and generate normative data for measuring emotional intelligence in the Peruvian context. A total 782 people participated, 175 men (22.4 %) and 607 women (77.6 %), between 18 and 59 years old (M=29.39, DE=9.67), selected through a non-probabilistic convenience sampling. First, the metric quality of its 16 items was verified. Then, its internal structure was analyzed through confirmatory factor analysis, finding adequate fit indices for the bifactor model: χ2=305.795, CFI=.969, TLI=.958, RMSEA=.056 y SRMR=.029, in addition to evidence in favor of its unidimensionality: PUC, ωh and H coefficient >.80, ECV >.60 and explained variance of 71.97%. Likewise, evidence of its discriminant validity was found in relation to the scores of psychological discomfort measured with the K10 Scale (r=-.37, r2=.13). Also, the reliability evidence was verified by the internal consistency method for the general scale (ω=.947) and the four specific factors (SEA=.833, OEA=.798, UOE=.886, ROE=.891). Finally, evidence of equity was found according to sex and age group (ΔCFI<.010) and RMSEA (ΔRMSEA<.015). Therefore, normative data were developed for the general adult population. In conclusion, the WLEIS-S Scale is a useful instrument to measure emotional intelligence in the Peruvian context.